Genome characterization of Iranian sophora yellow stunt virus isolates and construction of infectious clones - Esmaeili, Maryam; Heydarnejad, Jahangir; Hasanvand, Vahid; Massumi, Hossain; Kvarnheden, Anders; Varsani, Arvind (Plant pathology, 2023)
Sophora yellow stunt virus is a species of the genus Nanovirus. Sophora yellow stunt virus (SYSV) has a wide geographical distribution in Iran. In the current study, SYSV was identified from Kerman province (south‐eastern Iran) in five symptomatic aromatic herbs that are commonly used in the Iranian diet: parsley, dill, fenugreek, mint and basil. These infections were detected using either a PCR assay or high‐throughput sequencing. Eight circular single‐stranded DNA genomic components of five SYSV isolates as well as a new sophora isolate from south‐western Iran were PCR amplified, sequenced and characterized. Sequence analysis of SYSV genomic components showed that the Iranian isolates shared nucleotide identities of 64%–100% with each other and 63%–93% with an isolate from China. DNA‐Rs and DNA‐Cs were found to be the most diverse components relative to the others. Furthermore, associated alphasatellite molecules with the basil sample shared nucleotide identities of 80.7%–99.9% with the counterpart alphasatellite molecules in GenBank. Infectious clones for the genomic DNAs of SYSV were constructed using head‐to‐tail dimeric or partial dimeric inserts. The pathogenesis of SYSV was demonstrated by inoculation with the infectious DNA clones that induced typical symptoms in five plant species. Given the wide distribution of SYSV and its common host (Sophora alopecuroides) throughout Iran, as well as detection of the virus in plants of four families (Fabaceae, Apiaceae, Lamiaceae and Nitrariaceae), this virus is of economic importance within leguminous crops and in production of aromatic herbs in Iran. Sophora yellow stunt virus was identified in five symptomatic aromatic herbs in Iran followed by construction of infectious cloned genome components and demonstration of the viral pathogenesis by fulfilling Koch's postulates.